Role of small and medium sized enterprises in the regional development of Croatia - Zlatan Frohlich; Sanja Malekovic; Mario Polic (European Regional Science Association (ERSA), 1998)
The paper will reflect upon the crucial role of small and medium sized enterprises (SME's) in Croatia's local and regional development, particulary in circumstances when the Croatian counties (regions) are simultaneously faced with problems related to post-war reconstruction, economic transition, industrial restructuring and future development. The paper will point out the main goals related to the development of the SME sector in Croatia as well as the importance of their development for particular categories of regions (counties affected by the war, border regions, industrial decline regions, etc.). The basic problems and needs of the entrepreneurs in these regions will be considered (on the basis of in depth surveys and interviews which are carried out in pilot regions). Furtherrmore, the paper will provide a survey of proposed policy measures aiming to encurage the start-up of new small firms, as well as further development of the already existing innovative industrial small firms - thus contributing to regional restructuring and development of Croatia's "problem regions".
Keywords: 330